Cosa “inscrive” una macchina? Alcune ipotesi su tecnica e scienza - Laino, Luigi (Mechane, 2024)
In this paper, I will analyse the import of the concept of “machine” for the emergence of scientific knowledge. After a short introduction, I will provide, in the second section, a definition of technology that bears on the verification of theory, but not in the sense that it realises theory in practice. Rather, I aim to show that technology is the counterpart of theory. In the third section, by leveraging the distinction between apotelestic and sympleromatic machines, I will show that “scientific” machines are mostly sympleromatic, as well as I will compare the Antikythera mechanism with contemporary colliders, in order to explain why and how a machine “represents” a theory. In the fourth section, I will reflect on the origin and meaning of science and the role and essence of machines.